sCTLA-4, CD4+CD25+Foxp3+ regulatory T cells in Behçet's disease patients - Demir, N.; Ilhan, F.; Demir, T.; Godekmerdan, A. (My University, 2012)
[Abstract Not Available]
Keywords: Behcet Syndrome; Biological Markers; Case-Control Studies; CD4 Lymphocyte Count; CTLA-4 Antigen; Forkhead Transcription Factors; Humans; Immunosuppressive Agents; Interleukin-2 Receptor alpha Subunit; Remission Induction; T-Lymphocytes, Regulatory; Treatment Outcome; azathioprine; CD4 antigen; colchicine; cyclosporin A; cytotoxic T lymphocyte antigen 4; interleukin 2 receptor alpha; prednisolone; salazosulfapyridine; transcription factor FOXP3; biological marker; CTLA4 protein, human; cytotoxic T lymphocyte antigen 4; forkhead transcription factor; FOXP3 protein, human; IL2RA protein, human; immunosuppressive agent; interleukin 2 receptor alpha; arthritis; Behcet disease; CD4+ CD25+ FoxP3+ T lymphocyte; CD4+ CD25+ T lymphocyte; cell count; cell function; cell loss; clinical article; controlled study; disease duration; human; letter; priority journal; protein blood level; protein expression; regulatory T lymphocyte; remission; urogenital ulcer; uveitis; blood; case control study; CD4 lymphocyte count; drug effect; immunology; metabolism; treatment outcome